Thickness effect on the optical and morphological properties in Al2O3/ZnO nanolaminate thin films prepared by atomic layer deposition. (February 2016) - López, J.; Martínez, J.; Abundiz, N.; Domínguez, D.; Murillo, E.; Castillón, F.F.; Machorro, R.; Farías, M.H.; Tiznado, H.
Abstract: In this work, we studied the optical and morphological properties of ultrathin nanolaminate films based on Al2 O3 /ZnO (AZ) bilayers stack. The films were deposited on Si (100) by means of thermal atomic layer deposition (ALD) technique. The bilayer thicknesses (ratio = 1:1) were 0.2, 1, 2, 4, 10 and 20 nm. Refractive index (n) and band gap (Eg ) of each nanolaminate were studied via spectroscopic ellipsometry (SE), and spectral reflectance ultraviolet–visible spectroscopy (UV–vis). Surface morphology and roughness parameters of the nanolaminates were measured by Atomic Force Microscopy (AFM). The optical and morphological properties were shown highly dependent on the bilayer thickness. Ellipsometric data treated through the Cody–Lorentz optical model revealed that the refractive index decreases for thinner bilayers. A sharp intensity decay of refractive index and peaks at the UV region (200–400 nm) indicated increased transparency for thinner bilayers. It is also shown that the band gap is tunable. The maximum band gap value was 4.8 eV. These results reveal that ZnO combined with Al2 O3 as bilayers stack can be converted into a dielectric material with enhanced band gap, opening the possibility for new optical and dielectric applications. Highlights: Nanolaminates of Al-ZnO grown by ALD shown that optical and morphological properties are dependent on the bilayer thickness. Refractive index and the optical band gap of nanolaminates can be be modulated by controlling the thickness in the bilayers. This work reveal that ZnO can transform in dielectric material when it combines with Al2 O3 via enhancement of the band gap.